1995
DOI: 10.1111/j.1365-2249.1995.tb05560.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in urinary cytokines and soluble intercellular adhesion molecule-1 (ICAM-1) in bladder cancer patients after Bacillus Calmette—Guérin (BCG) immunotherapy

Abstract: SUMMARY Intravesical immunotherapy for carcinoma in situ of the bladder is arguably the most effective form of tumour immunotherapy described to date. Following repeated instillations of BCG organisms into the bladder, large quantities of cytokines are detected in patients’ urine. This study concerns the production of IL‐1β, IL‐2, IL‐4, IL‐6, IL‐8, IL‐10, tumour necrosis factor‐alpha (TNF‐α), interferon‐gamma (IFN‐γ) and soluble ICAM‐1 (sICAM‐1) throughout the six weekly instillations which comprise a therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
9

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 29 publications
2
64
0
9
Order By: Relevance
“…In particular, neutrophils and inflammatory monocytes are believed to be critical effector cells, capable of mediating the observed tumor immunity. [12][13][14][15][16] Specifically, innate cells have the capacity to degranulate in response to exposure to BCG, resulting in the bystander killing of tumor cells. 17 In support of this model, it has been demonstrated that BCG treatment induces surface expression of TRAIL on neutrophils, thus arming them with the capacity to induce tumor cell death.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, neutrophils and inflammatory monocytes are believed to be critical effector cells, capable of mediating the observed tumor immunity. [12][13][14][15][16] Specifically, innate cells have the capacity to degranulate in response to exposure to BCG, resulting in the bystander killing of tumor cells. 17 In support of this model, it has been demonstrated that BCG treatment induces surface expression of TRAIL on neutrophils, thus arming them with the capacity to induce tumor cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Several cytokines have been implicated in this cell-mediated response, including interleukin (IL)-1, IL-2, IL-6, IL-8, IL-10, IL-12, tumor necrosis factor-, and IFN. 11 This has been demonstrated by analysis of urine following administration of BCG. IL-1, IL-6, and IL-8 are increased after the first BCG instillation 12,13 .…”
Section: Mechanism Of Action Of Bcgmentioning
confidence: 96%
“…The presence of soluble TRAIL in the granule fraction is consistent with its rapid release into culture supernatants following stimulation with BCG and also the inability of actinomycin D and cycloheximide to inhibit TRAIL secretion. However, the findings that IFN treatment induces de novo synthesis of TRAIL [19] that accumulates in secretory vesicles [22], suggest that IFN present in the urine either during BCG therapy [29,30] or supplied exogenously [31] may augment the total amount of TRAIL released by PMN and contribute to the sustained secretion of TRAIL after preformed intracellular stores are expended.…”
Section: Mechanisms Of Trail Release By Pmnmentioning
confidence: 99%